Women's beliefs about breast cancer causation in a breast cancer case-control study - Lizama, N.; Rogers, P.; Thomson, Allyson; Slevin, Terry; Fritschi, L.; Saunders, C.; Heyworth, J. (John Wiley and Sons Ltd, 2015)
Objective: Our study sought to ascertain women's beliefs about breast cancer risk factors and whether these beliefs differed by demographic factors and personal and family history of breast cancer. Methods: Participants in a case-control study of breast cancer rated the effect of 37 exposures on the risk of being diagnosed with breast cancer. Chi-square tests were undertaken to measure differences in responses between cases and controls for each exposure. Logistic regression was undertaken to ascertain whether demographic factors and personal and family history of breast cancer affected participants' ability to correctly identify known breast cancer risk factors. Results: A total of 2742 participants completed the questionnaire, comprising 1109 cases and 1633 controls. Significant differences (p<0.05) between cases and controls were found for 16 of the 37 exposures. Younger women and university-educated women were more likely to correctly identify known breast cancer risk factors. Women's perceptions about the effect of alcohol consumption on breast cancer risk, particularly regarding red wine, differed from that reported in the literature. Conclusions: Beliefs about risk factors for breast cancer may differ between cases and controls. Public health initiatives aimed at increasing awareness of breast cancer risk factors should consider that women's beliefs may differ by demographic factors and family history of breast cancer.